DINAMIKA PEMBAURAN HUKUM ISLAM DI PALEMBANG: MENGURAI ISI UNDANG-UNDANG SIMBUR CAHAYA - Adil, Muhammad (Nurani, 2014)
Abstract: Jurisprudence is one of the disciplines that become facts of history in appreciating the local culture. In this context, true Islamic law should be interpreted as a process, not a product monumental. Islamic law has characteristics very different from the law in the sense of modern jurisprudence. Islamic law was developed based on the revelation, in addition to human thought and also colored by local feature in addition to the universal characteristics. This article will discuss the dynamics of assimilation of Islamic law in Palembang with a case study Undang-Undang Simbur Cahaya.ملخص: الفقه هو واحد من التخصصات التي تصبح حقائق التاريخ في تقدير الثقافة المحلية. وفي هذا السياق، ينبغي تفسير الفقه صحيح لأن عملية وليس منتج ضخمة. الفقه أو الشريعة الإسلامية لها خصائص مختلفة جدا عن القانون بالمعنى الفقهي الحديث. وقد وضعت الشريعة الإسلامية على أساس الوحي، بالإضافة إلى الفكر البشري والملونة أيضا ميزة المحلية بالإضافة إلى خصائص عالمية. هذه المادة سوف تدرس ديناميات استيعاب الشريعة الإسلامية في دراسة حالة باليمبانج باليمبانج القانون العرفي. Kata Kunci: undang-undang simbur cahaya, hukum adat.